2011
DOI: 10.1007/s00296-010-1766-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyarteritis nodosa and Henoch–Schönlein purpura nephritis in a child with familial Mediterranean fever: a case report

Abstract: Familial Mediterranean fever is an autosomal recessive disease characterized by recurrent self-limited attacks of fever accompanied by peritonitis, pleuritis, and arthritis. Approximately 5% of individuals with familial Mediterranean fever have been reported to have Henoch-Schonlein purpura and about 1% to have polyarteritis nodosa. A 7-year-old girl presenting with complaints of purpuric rash, abdominal pain, arthritis, hematuria, and proteinuria and having IgA depositions on renal biopsy was diagnosed as Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Based on the data of Turkish FMF study group (18), the incidences of HSP and PAN are 2.7% and 0.9%, respectively. There was a case report in which the concomitance of HSP and PAN responding to intravenous immunoglobulin therapy was reported in a pediatric FMF patient (50).…”
Section: (E) Other Involvements and Amyloidosismentioning
confidence: 99%
“…Based on the data of Turkish FMF study group (18), the incidences of HSP and PAN are 2.7% and 0.9%, respectively. There was a case report in which the concomitance of HSP and PAN responding to intravenous immunoglobulin therapy was reported in a pediatric FMF patient (50).…”
Section: (E) Other Involvements and Amyloidosismentioning
confidence: 99%
“…Additionally, heterozygous mutations in exon 2 of the MEFV gene act as disease-severity modifiers in inflammatory diseases such as arthritis (Lachmann et al 2006). Autoinflammatory gene mutations have also been described in patients affected with vasculitis; autoinflammatory gene mutations in these patients are known to modify disease severity, response to agents, and/or clinical manifestations (Atagunduz et al 2003;Girisgen et al 2012). SLE is caused by multiple genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In Henoch-Schönlein purpura some authors (Heldrich et al, 1993, Rostoker et al, 1995, Ruellan et al, 1997) administered low-dose or lower limit of high-dose regimens, others (Rostoker et al, 1994, Lamireau et al, 2001, Fagbemi et al, 2007 strictly apply 2 g/kg. Apart from the dose applied all authors emphasize dramatic improvement of IVIG treatment already after 24 hours after beginning (Girisgen et al, 2011). It could be supposed that patients who respond to high-dose IVIG therapy would probably also respond to much lower doses, in many rheumatological indications vasculitides not excluded.…”
Section: Conditionmentioning
confidence: 99%
“…Asano et al (2006) postulated that the effect of IVIG therapy on PAN is temporary, but in situation that PAN is induced by infections, IVIG therapy leads to a complete remission of the disease due to the neutralization of immune activation triggers, such as Parvovirus B19 and Streptococcus. Also Girisgen et al (2011) based on the case report of 7 years old girl with polyarteritis nodosa and Henoch-Schönlein purpura nephritis suggested that IVIG might be an important adjunct therapy in selected patients with polyarteritis nodosa, especially in the lack of response to steroids and immunosuppressive drugs. On the contrary González-Fernández & García-Consuegra (2007) published the case-report of a child with polyarteritis nodosa that was unresponsive to conventional treatment, as well as IVIG treatment during her first and second hospitalizations.…”
Section: Polyarteritis Nodosamentioning
confidence: 99%